PICTORICAL WARNING PADA KEMASAN ROKOK: KOMUNIKASI PERSUASIF DALAM KAMPANYE KESEHATAN - Negoro, Sherly Hindra (Informasi, 2016)
Smoking has became the serious problem which always to be the classical dynamic ofhealth communication's field. Through health campaign by using pictorical warning incigarette packs, Indonesian Government has priority to reduce the number of smokersin Indonesia. Pictorical warning in cigarette packs was regard as one of communicationstrategic for implementing. Health campaign has outcome that could change thehealth behavior for the persuadee. Visualization by using image becomes persuasivecommunication tools cigarette packs as the communication media. EPPM model wasused to analysis this case. This paper was using literature study to understand thisproblem.